Soluble epoxide hydrolase in the generation and maintenance of high blood pressure in spontaneously hypertensive rats - Maarten P. Koeners; Sebastiaan Wesseling; Arzu Ulu; R López-Sepúlveda; Christophe Morisseau; Branko Braam; Bruce D. Hammock; Jaap A. Joles (2011)
We hypothesized that perinatal inhibition of soluble epoxide hydrolase (SEH), which metabolizes epoxyeicosatrienoic acids in the arachidonic acid (AA) cascade, with an orally active SEH inhibitor, 12-(3-adamantan-1-yl-ureido)-dodecanoic acid (AUDA), would persistently reduce blood pressure (BP) in adult SHR despite discontinuation of AUDA at 4 wk of age. Renal cytoplasmic epoxide hydrolase-2 (Ephx2) gene expression was enhanced in SHR vs. WKY from 2 days to 24 wk. Effects of perinatal treatment with AUDA, supplied to SHR dams until 4 wk after birth, on BP in female and male offspring and renal oxylipin metabolome in female offspring were observed and contrasted to female SHR for direct effects of AUDA (8-12 wk). Briefly, inhibition of SEH was effective in persistently reducing BP in female SHR when applied during the perinatal phase. This was accompanied by marked increases in major renal AA epoxides and decreases in renal lipoxygenase products of AA. Early inhibition of SEH induced a delayed increase in renal 5-HETE at 24 wk, in contrast to a decrease at 2 wk. Inhibition of SEH in female SHR from 8 to 12 wk did not reduce BP but caused profound decreases in renal 15(S)-HETrE, LTB4, TBX2, 5-HETE, and 20-HETE and increases in TriHOMEs. In male SHR, BP reduction after perinatal AUDA was transient. Thus, Ephx2 transcription and SEH activity in early life may initiate mechanisms that eventually contribute to high BP in adult female SHR. However, programmed BP-lowering effects of perinatal SEH inhibition in female SHR cannot be simply explained by persistent reduction in renal SEH activity but rather by more complex and temporally dynamic interactions between the renal SEH, lipoxygenase, and cyclooxygenase pathways.